PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tiana, Alma; Bustang, Bustang; Sabarudin, Sabarudin (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to determine the Effect of Working Capital Turnover on the Profitability of Manufacturing Companies Listed on the Indonesia Stock Exchange